Calculation of a heat exchanger using heat pipes in the exhaust air heat recovery system - A. S. Zaitsev; M. V. Shamarov; R. A. Zhlobo; E. O. Ivchenko (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the work is to develop practical recommendations for the design and manufacture of a heat exchanger using heat pipes, which could find widespread use in heating, ventilation and air conditioning systems at facilities for various purposes. Method. The research is based on methods of thermodynamic analysis, full-scale and computational modeling of processes and objects of refrigeration and cryogenic technology, air conditioning and life support systems. Result. The implementation of the practical recommendations studied in the work on the use and design of heat exchangers using heat pipes in ventilation, heating and air conditioning systems will provide significant savings in energy spent on heating and/or cooling the air supplied to the room served by the HVAC system. To reduce heat loss in a building, it is rational to maintain air balance and compensate for the exhaust air with an organized influx of outside air, to heat which the heat of the removed exhaust air is utilized. Conclusion. Compared to a heat exchanger based on a glycol recuperator, a regenerator using heat pipes is less energy-intensive, requires virtually no maintenance, and is also more energy efficient due to the absence of a pumping device that requires electricity in the design. At the same time, the ability to completely separate the supply and exhaust ventilation flows of the regenerator on heat pipes is preserved, which is extremely in demand in medical institutions, due to the need to comply with strict sanitary standards.